Integrative review protocol for Indigenous youth participation in health equity promotion - Janice Linton; Darrien Morton; Andrew R Hatala (BMJ Open)
Introduction Indigenous youth participation in decision-making is internationally recognised as a pathway to promote health equity, decolonisation and social inclusion. Hearing Indigenous youth voices and actively involving them in decisions that affect their lives and their communities has the potential to address disproportionate health and social challenges they encounter. Yet the existing evidence-base on participatory approaches remains fragmented and vast leading to a lack of integration.Methods and analysis An integrative review methodology will be used to conduct a comprehensive, multidisciplinary review of the literature about Indigenous youth participation in health equity promotion. The literature search is anticipated to be carried out in July–August 2022. We will search online databases Scopus, Ovid MEDLINE, Embase and PsycINFO along with several interdisciplinary databases indexed in EBSCOhost and ProQuest. Key Indigenous research journals not consistently indexed in the online databases will be examined to identify additional journal articles. We will employ a blinded, dual-reviewer two-step selection process with established inclusion/exclusion criteria and limit data to English-language publications related to Indigenous populations in Canada, USA, Aotearoa New Zealand and Australia. Focusing on qualitative empirical and theoretical studies, they will undergo quality appraisal and Covidence software will be used to manage the review. Data will be sorted, extracted and analysed. We will codify data for descriptive reporting and conduct a narrative synthesis to identify a common conceptualisation for Indigenous youth participatory approaches across disciplines, its barriers and facilitators, and knowledge gaps.Ethics and dissemination Ethical review is not required for the integrative review. The review will be shared through various publication and non-academic platforms as well as our university and community research networks. Findings will have broad relevance for those seeking to involve Indigenous youth to be active decision-makers across a range of fields, but with specific implications for health equity.